Beyond bilateralism : U.S.-Japan relations in the new Asia-Pacific - Krauss, Ellis S.; Pempel, T. J., 1942- (Contemporary issues in Asia and the Pacific., 2004)
This is the first comprehensive analysis of the ways in which changes in the geopolitical context have altered the nature of the long-stable U.S.-Japan relationship: much of what had once been a bilateral and relatively exclusive relationship has been transformed in the past two decades. The authors present eleven case studies of important domains--ranging from increased flows of private capital to international security concerns to the growing importance of multilateral organizations--in which the relationship has been altered to a greater or lesser degree. Individual chapters present new ways of understanding international financial flows, U.S.-Japan trade relations, and U.S.-Japan manufacturing rivalry. Others present very cogent synthetic analyses of the changing context of U.S.-Japan relations. Together they provide an account of the bilateral, regional, and global institutions--political, military, and financial--that dominate the geopolitics of U.S.-Asia relations. Although written to a consistently high intellectual level, the chapters in this timely volume are intended for a nonspecialist audience and will be useful to practitioners in business and government, as well as to students and teachers.